Genetic resources of some representatives of the genus Allium L. - M. I. Ivanova; A. V. Polyakov; A. I. Kashleva (Овощи России, 2025)
Since ancient times, species of the genus Allium have played a significant role in the human diet, in traditional medicine for the treatment of many diseases and in official medicine as raw materials, as well as medicinal and prophylactic agents. Phytochemicals such as organosulfur compounds, phenolic compounds, fatty acids and saponins are associated with the antioxidant and antimicrobial properties of these species, among many other biologically active substances. All parts of the plant, including the bulb, leaf, pseudostem, root, flower and seed, exhibit antioxidant properties in in vitro assays. Characteristic phytocompounds that contribute to the antimicrobial activity of onion crops include allicin, ajoene, allyl alcohol and some diallyl sulfides. Nanoparticles synthesized using Allium species are also known for their notable antimicrobial properties. Allium species are a product with high nutritional value, and due to secondary metabolites, it is also used to protect plants with various products created on the basis of its biologically active components. Allium species are valued for their unique macroelement composition and are used as popular vegetables and spices. In the Russian Federation, there is significant biological and morphological diversity of cultivated and wild onion species. Over the past few years, an extensive program of collecting and studying Allium species has been carried out at VNIIO – a branch of the FSBSI Federal Scientific Vegetable Center. High morphological and biochemical variability of the studied species has been established, which can be used in breeding programs and when growing varieties.